1982
DOI: 10.1113/jphysiol.1982.sp014045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of duodenal cannulation on abomasal emptying and secretion in the preruminant calf.

Abstract: SUMMARY1. The effect of re-entrant cannulation of the duodenum on digesta flow from, and secretion into, the abomasum of the preruminant calf was studied.2. Calves fitted with abomasal cannulas and, at the same time or later, with re-entrant duodenal cannulas were given, by abomasal infusion, test feeds containing glucose and minerals. Net volumes of secretary fluids entering the abomasum and amounts of digesta flowing to the duodenum were estimated from changes in concentrations of water soluble markers (phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…We do not believe that the presence of an abomasal cannula altered the emptying rate in the calves in our study because placement of a percutaneous endoscopic gastrostomy tube did not slow gastric emptying in cats, 66 and the presence of the much more invasive duodenal reentrant cannula did not alter abomasal emptying rate in milk-fed calves. 67 In conclusion, in contrast to the conclusion of previous studies 25,26 in calves, our results indicate that the effects of osmolarity and glucose concentration on abomasal emptying rate in euhydrated calves are similar to those in euhydrated monogastric animals. Whether slowing of the abomasal emptying rate in dehydrated diarrheic calves suckling an electrolyte solution is clinically important remains to be determined.…”
Section: Discussioncontrasting
confidence: 99%
“…We do not believe that the presence of an abomasal cannula altered the emptying rate in the calves in our study because placement of a percutaneous endoscopic gastrostomy tube did not slow gastric emptying in cats, 66 and the presence of the much more invasive duodenal reentrant cannula did not alter abomasal emptying rate in milk-fed calves. 67 In conclusion, in contrast to the conclusion of previous studies 25,26 in calves, our results indicate that the effects of osmolarity and glucose concentration on abomasal emptying rate in euhydrated calves are similar to those in euhydrated monogastric animals. Whether slowing of the abomasal emptying rate in dehydrated diarrheic calves suckling an electrolyte solution is clinically important remains to be determined.…”
Section: Discussioncontrasting
confidence: 99%
“…36 We do not believe that the presence of an abomasal cannula altered emptying rate in the study calves because the placement of a percutaneous endoscopic gastrostomy tube does not slow gastric emptying in cats 37 ; furthermore, compared with an abomasal cannula, the presence of a much more invasive duodenal reentrant cannula does not alter emptying rate in milk-fed calves. 38 Ultrasonographic measurements indicate the change in stomach volume with time, whereas scintigraphic measurements indicate the rate of disappearance of a radioactive agent from the stomach. 11 At any time, the abomasal volume in calves is the sum of the preprandial volume, suckled volume, and volume of fluids secreted by the salivary glands and abomasum, minus the volume emptied from the abomasum.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the cannula may physically restrict or change the course of digesta flow, because peristaltic contractions failed to propagate beyond the reentrant cannula (Wenham and Wyburn, 1980). Nevertheless, Sissons and Smith (1982) observed that inserting a reentrant cannula in the proximal duodenum of the preruminant calf did not lead to major disturbances in net abomasal secretion and digesta flow to the duodenum. CONCLUSION When preruminant calves were fed a milk diet, ingested caseins were mainly (92-94%) retained in a clot and released progressively from the stomach as peptides.…”
Section: Discussionmentioning
confidence: 99%